Fabrication of Carboxylate‐Functionalized 2D MOF Nanosheet with Caged Cavity for Efficient and Selective Extraction of Uranium from Aqueous Solution - Yu, Cai‐Xia; Jiang, Wen; Lei, Min; Yao, Meng‐Ru; Sun, Xue‐Qin; Wang, Yanlong; Liu, Wei; Liu, Lei‐Lei (Small (Weinheim an der Bergstrasse, Germany), 2024)
The efficient removal of radioactive uranium from aqueous solution is of great significance for the safe and sustainable development of nuclear power. An ultrathin 2D metal–organic framework (MOF) nanosheet with cavity structures was elaborately fabricated based on a calix[4]arene ligand. Incorporating the permanent cavity structures on MOF nanosheet can fully utilize its structural characteristics of largely exposed surface area and accessible adsorption sites in pollutant removal, achieving ultrafast adsorption kinetics, and the functionalized cavity structure would endow the MOF nanosheets with the ability to achieve preconcentration and extraction of uranium from aqueous solution, affording ultrahigh removal efficiency even in ultra‐low concentrations. Thus, more than 97% uranium can be removed from the concentration range of 50–500 µg L−1 within 5 min. Moreover, the 2D nano‐material exhibits ultra‐high anti‐interference ability, which can efficiently remove uranium from groundwater and seawater. The adsorption mechanism was investigated by X‐ray photoelectron spectroscopy (XPS), Fourier transform infrared (FT‐IR) analysis, and density functional theory (DFT) calculations, which revealed that the cavity structure plays an important role in uranium capture. This study not only realizes highly efficient uranium removal from aqueous solution but also opens the door to achieving ultrathin MOF nanosheets with cavity structures, which will greatly expand the applications of MOF nanosheets. A carboxylate‐functionalized 2D metal–organic framework (MOF) nanosheet with cage‐like cavities was constructed based on the calix[4]arene, which not only facilitates MOF exfoliation and pollutant capture but also prevents pollutant desorption. The as‐synthesized MOF nanosheets show an ultrahigh selectivity and anti‐interference performance for uranium.